2020
DOI: 10.2478/msp-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of color quality and luminous flux for remote-phosphor LEDs with red-emitting CaMgSi2O6:Eu2+,Mn2+

Abstract: SiO2 particles and red-emitting CaMgSi2O6:Eu2+,Mn2+ phosphor have been added into a yellow phosphor compound YAG:Ce3+ to enhance the optical efficiency of white light LEDs whose average correlated color temperature (CCT) is in the range of 5600 K ÷ 8500 K. It was observed that altering CaMgSi2O6:Eu2+,Mn2+ concentration from 2 % to 30 % while maintaining 5 % of the SiO2 strongly influenced the color rendering index (CRI), color quality scale (CQS), and lumen efficiency of the compound. Besides, through the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…They can especially be served as an alternative solution to halogen, incandescent, and fluorescent illuminating systems since they are safer and sturdier. Researchers also pointed out that LEDs potentially have better energy conversion efficiency leading to less heat release, longer lifetime, and more stable brightness performance (Nguyen et al, 2021a;Luo et al, 2020). A LED package was conventionally fabricated utilizing the synthetic of a blue chip and a yellow phosphor material.…”
Section: Introductionmentioning
confidence: 99%
“…They can especially be served as an alternative solution to halogen, incandescent, and fluorescent illuminating systems since they are safer and sturdier. Researchers also pointed out that LEDs potentially have better energy conversion efficiency leading to less heat release, longer lifetime, and more stable brightness performance (Nguyen et al, 2021a;Luo et al, 2020). A LED package was conventionally fabricated utilizing the synthetic of a blue chip and a yellow phosphor material.…”
Section: Introductionmentioning
confidence: 99%
“…With the presence of these QDs, it is possible to generate white illuminations with adjustable CCTs when the R a values are from 96 to 97, and LLE values are from 243 lm/W to 254 lm/W, under the CCT range of 2700-6500 K [9]. A study suggested a R/Y/C WLED package, in which the combination of the red AlGaInP LED, the pc-Y LED, and pc-C LED devices were demonstrated, for the white-illuminating generation with adjustable CCTs through several R a , R 9 , and LLE values under two CCT ranges of 2700-6500 K and 2731-6533 K [10]. In that work, pc-Y LED and pc-C LED parts utilized blue InGaN LED dyes, but the phosphors were different.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pc-LED products provide considerable energy-consumption reduction, lower maintenance costs, high resistance, long-life performance, and limitation of carbon and UV emissions [3]. Thus, LED has been gradually cementing its position in solid-state lighting (SSL) [4].…”
Section: Introductionmentioning
confidence: 99%